2014
DOI: 10.1371/journal.pone.0092985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Seasonal Soil Microbial Process in Snow-Covered Temperate Ecosystems of Northern China

Abstract: More than half of the earth's terrestrial surface currently experiences seasonal snow cover and soil frost. Winter compositional and functional investigations in soil microbial community are frequently conducted in alpine tundra and boreal forest ecosystems. However, little information on winter microbial biogeochemistry is known from seasonally snow-covered temperate ecosystems. As decomposer microbes may differ in their ability/strategy to efficiently use soil organic carbon (SOC) within different phases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…However, microbial activity has been shown to persist during winter under insulating layers of snow and in sub-zero temperatures (Zhang et al, 2014). Modelling also predicted sustained organic substrate degradation, microbial turnover and net heterotrophy during the winter (Fig.…”
Section: Net Ecosystem Metabolism and Carbon Budgetmentioning
confidence: 87%
“…However, microbial activity has been shown to persist during winter under insulating layers of snow and in sub-zero temperatures (Zhang et al, 2014). Modelling also predicted sustained organic substrate degradation, microbial turnover and net heterotrophy during the winter (Fig.…”
Section: Net Ecosystem Metabolism and Carbon Budgetmentioning
confidence: 87%
“…We calculated the total lipids as an indicator of microbial biomass [ 47 ]. The details of the method can be seen in [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…As decomposer microbes might differ in their ability or strategy to efficiently use SOC within different phases of the year [ 13 16 ], the temperature sensitivity of SOC decomposition might differ across different seasons [ 11 ]. Previous studies have demonstrated a distinct transition in the microbial community structure and function from winter to summer [ 17 19 ]. For instance, in the temperate area of north China, a shift in soil microbial community composition occurred with higher fungal: bacterial biomass ratio and gram negative (G-): gram positive (G+) bacterial biomass ratio in winter than in summer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature may cause decline of CAZymes activities in the cold season compared to the activities in the warm season in both boreal coniferous forest [ 30 ] and in temperate spruce forest [ 31 ], and thus also negatively affect C cycling. Changes in the C cycling by microbial community and in the composition of microbial community were observed between summer and winter in mixed temperate forest [ 32 ] as well as in an arctic system [ 33 ]. Dominance of saprotrophic fungi, which are largely responsible for degradation of lignocellulose [ 34 ], in spring and ECM fungi, which are involved in plant derived C storage in soil [ 3 ], in late summer was shown for the temperate and boreal forests [ 35 39 ].…”
Section: Introductionmentioning
confidence: 99%